Characterization of Pseudomonas cepacia isolates from patients with cystic fibrosis. - McKevitt, A I (1984)
Pseudomonas cepacia infections which follow a fulminant course and which include septicemia are being reported with increasing frequency from cystic fibrosis patients. Forty-eight P. cepacia isolates from cystic fibrosis patients were screened for production of potential virulence factors. A majority of strains tested produced protease and lipase. Eleven strains harbored plasmids of approximate molecular weights in the range 50 X 10(6) to 100 X 10(6). Twenty-two strains produced a smooth lipopolysaccharide. Studies are presently under way to determine the role of these potential virulence factors in the pathogenesis of P. cepacia disease.